Optimasi Persediaan Bahan Baku Tepung Terigu dengan Metode Economic Order Quantity (EOQ) pada Celebriti Bakery - NI LUH ERNA WATI; RATNA KOMALA DEWI; NI WAYAN PUTU ARTINI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2020)
Optimization of Wheat Flour Raw Material Inventory with The Economic Order Quantity (EOQ) Method at Celebriti Bakery Raw material inventory control is important to determine and guarantee the availability of raw materials in the right quantity and time. Wheat flour is the main raw material that are used and hence highest expenditure at Celebriti Bakery. This study aims to determine the actual inventory control of wheat flour, the economical inventory control of wheat flour with the Economic Order Quantity (EOQ) method, and potential cost savings of wheat flour inventory at Celebriti Bakery. The study was conducted using descriptive and quantitative methods. Based on study result, Celebriti Bakery orders 1.750 kg of wheat flour per order with purchase frequency of 34 times. Celebriti Bakery sets safety stock of 200 kg, reorders when the supply is 250 kg, and has maximum inventory of 2.000 kg. The EOQ method suggests the economic order is 3.111 kg per order with purchase frequency 19 times. The analysis suggests 161,13 kg safety stock, 322,26 kg reorder point and 3.272,13 kg maximum inventory. Celebriti Bakery currently spends Rp 3.406.140,00 for wheat flour inventory cost. The EOQ method shows potential cost saving of Rp 526.805,00 or 15%. Celebrity Bakery needs to optimize the supply of wheat flour with the EOQ method to save the cost of wheat flour inventory.